Markets, mis‐direction and motives: A factual analysis of hoarding and speculation in southern Murray–Darling Basin water markets. (17th February 2021) - Loch, Adam; Auricht, Christopher; Adamson, David; Mateo, Luis
Abstract : There is a long history of concern about speculation in water markets, and potential adverse impacts on agricultural water users. However, applications of traditional analysis into price increase drivers in water markets are challenging due to data limitations. To address this, we use speculation theory, most notably Hirshleifer's four fundamentals for speculative trade, to examine whether speculation or hoarding price increase drivers are evident in Australia's largest water market, the southern Murray–Darling Basin. While speculation is likely, and with good reason given the gains possible, we find no evidence of hoarding behaviour in market price or volume trends. It is more plausible that agricultural sectors – notably horticultural users – have driven price increases given their requirements to access water at any cost during periods of low supply. These findings conform to theoretical expectations and help to inform badly needed insights into water market fundamentals required for future analysis. Overall, calls for stricter market controls on non‐agricultural water users are not supported by our findings. However, greater transparency in water market and broker activity, arising from substantial improvements in the underlying data and trade regulations associated with water markets, would be an ideal outcome from any public police extension.